2002
DOI: 10.1124/jpet.102.038166
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Linoleic Acid Metabolites on Cardiac Sodium Current

Abstract: 9,10-Epoxy-12-octadecenoic acid (EOA), a metabolite of linoleic acid, causes cardiac arrest in dogs. Other metabolites of linoleic acid also have toxic effects. This study investigates the mechanism of action of four of these compounds on cardiac Na ϩ current (I Na ). The whole-cell patch-clamp technique was used to investigate the effects of EOA, 9,10-dihydroxy-12-octadecenoic acid (DHOA), and their corresponding methyl esters (9,10-epoxy-12-octadecenoic methyl ester, EOM; and 9,10-dihydroxy-12-octadecenoic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…This effect can be largely blocked by administration of an sEH inhibitor (Smith et al 2005). The DiHOMEs exert a number of effects on mammalian cells including stimulating MCF-7 cell proliferation and acting as an endocrine disrupter (Markaverich et al 2005), modulating the sodium cation current in cardiac cells (Harrell and Stimers 2002), and increasing cellular oxidative stress (Viswanathan et al 2003). In mammalian cells, the DiHOMEs specifically inhibit mitochondrial function (Sisemore et al 2001;Moran et al 1997), suggesting one possible mechanism underlying EpOME-associated toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…This effect can be largely blocked by administration of an sEH inhibitor (Smith et al 2005). The DiHOMEs exert a number of effects on mammalian cells including stimulating MCF-7 cell proliferation and acting as an endocrine disrupter (Markaverich et al 2005), modulating the sodium cation current in cardiac cells (Harrell and Stimers 2002), and increasing cellular oxidative stress (Viswanathan et al 2003). In mammalian cells, the DiHOMEs specifically inhibit mitochondrial function (Sisemore et al 2001;Moran et al 1997), suggesting one possible mechanism underlying EpOME-associated toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Although cardiac and epithelial sodium channels are structurally unrelated, the data on cardiac sodium channels might point toward the distal tubule epithelial sodium channel as a possible target for inhibition by LA diols and triols. 19,20 Although the biological role and synthesis of LA-derived triols are uncharacterized in mammals, these metabolites are present in the urine 17 and are likely generated by the enzymatic rearrangement of linoleate hydroperoxides. 30 Other relevant findings suggesting associations between octadecanoids and hypertension have been reported recently.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7]10 In addition, in vitro studies have demonstrated that LA metabolites inhibit cardiac sodium channels. 19,20 Several studies in rats have shown the development of salt-sensitive hypertension with the inability to excrete an acute salt load after dietary LA acid deprivation that is corrected by administration of LA, suggesting that LA is intimately involved with renal sodium handling. 8,9 The results we report here reveal an increase in urinary excretion of LA diols and triols during intravenous salt loading that correlate with sodium excretion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it was once thought that sEH acted to render the leukotoxins safe by converting them to their diols, it now appears that the diols (including 12,13-DHOME) are the morepotent cytotoxins ( 29 ). Thus, inhibition of sEH ameliorates many of the toxic effects of the leukotoxins ( 39 ), whereas 12,13-DHOME adversely affects the electrophysiology of cells including oligodendrocytes ( 40 ) and cardiac myocytes ( 41 ). In addition, both 12(13)-and 9(10)-EpOME can be metabolized to the THF-diols ( Fig.…”
Section: Lc/msmentioning
confidence: 99%